2021
DOI: 10.3390/land10010055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Potentiality of Sentinel-2 for Change Detection Analysis Associated to LULUCF in Wallonia, Belgium

Abstract: Land Use/Cover changes are crucial for the use of sustainable resources and the delivery of ecosystem services. They play an important contribution in the climate change mitigation due to their ability to emit and remove greenhouse gas from the atmosphere. These emissions/removals are subject to an inventory which must be reported annually under the United Nations Framework Convention on Climate Change. This study investigates the use of Sentinel-2 data for analysing lands conversion associated to Land Use, La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In the case of optical products, image differencing was applied, a widely used technique for many applications involving change detection. Close et al [28] showed that image differencing achieves one of the highest overall accuracy scores (94%).…”
Section: Change Detectionmentioning
confidence: 99%
“…In the case of optical products, image differencing was applied, a widely used technique for many applications involving change detection. Close et al [28] showed that image differencing achieves one of the highest overall accuracy scores (94%).…”
Section: Change Detectionmentioning
confidence: 99%
“…Due to the potentially large number of earthquake-induced landslides, covering a wide area, multispectral Sentinel-2 imagery was selected. To identify landslides in pre-and post-Sentinel-2 Earthquake Imagery we used the Image Differencing approach (Lu et al, 2004) as detailed in Close et al (2021). Based on the assumption that earthquake-induced landslides would be highlighted on different spectral bands, we used a range of different approaches to attempt an automatic landslide detection.…”
Section: Optical-based Landslide Detectionmentioning
confidence: 99%
“…Since 2015, multispectral images of Sentinel-2 (S-2), Copernicus program are available with very good temporal (up to 2-3 days for middle latitudes) and spatial (10 m, 20 m) resolutions [14]. Moreover, the spectral characteristics of S-2 (13 spectral bands) make it a very valuable dataset for quasi-continuous monitoring of environmental changes [15], agricultural management [16] as well as for studying the structure and characteristics of forest communities [17,18].…”
Section: Introductionmentioning
confidence: 99%